Issuu on Google+

LÍMITES DE SUCESIONES 2 3  +  n n2  2n 2 − 3n + 5 5)  lim n → ∞ − 3n 2 + 6 n − 7  n →∞ 

( 2n + 5) 1)  lim n →∞

(

2 4)  lim − 5n + 8n − 6 n →∞

)

1000n + 7

lim

( 2n + 1) ( 5n + 3)

14)  lim

 n 2 + 2 n 2 + 2n    lim − 16)  n →∞  n − 1 n + 1  

2n − 17)  lim n→∞

lim

n→∞

(

n→∞

2

)

n+2

 3n 2 + 2n − 5  2 n −1 22)  lim   n →∞  4n 2 + n − 6     3n 2 − 4   25)  lim  n →∞ 2n 2 + n − 1    28)  lim 1 + n →∞

1  31)  lim 1 +  n →∞ n  34)  lim 1 − n →∞ 

 37)  lim 1 + n →∞ 

n −5

n

 n→∞ 

35)  lim 1 +

3   n − 3

 n3 + 3   40)  lim  3 n →∞ n − 7   

2 n + 3n + 5 n 29)  lim n +1 n→∞ 2 + 5 n−2  1 32)  lim 1 −  n→∞ n 

44  n n +1

n3

 n + 3  43)  lim   n →∞  n + 7  

n+ 2

n2 +n

3n − 2 46)  lim  5n − 3  n →∞ 5n + 4  

n

n  n 2 +1  2 

 n 2 − 5n + 9  n +1 26)  lim   n→∞   n + 10  2 n −1 5n + 2

)

n 3 − 3n 2 + 2 − n 3 + 1 20)  lim n→∞ n+2

−n

4n

1 1 1  + + ... + n  2 4 2 

4n 2 − 3n + 2

 n2 + 3 23)  lim  − n →∞  2n − 1 

)

3n 2 + 5n − 4

12)  lim n →∞

18) 

lim

n→∞

n5 − 6 + n + 7 4

n 2 + 3n + 1

n →∞ 6

2n 3 − n + 5

15)  lim

4n 2 − 3

(

2n + 3n − 3 − 2n + 7 2

3

− 5n

− 7n n + 5n + 6 n − 3 n →∞ 11n n − 4 n + 10

8n 2 − 5n n + 3n + 2 11)  lim n →∞ 6n n − 2n + 5

( 3n + 1) 3 − ( 3n − 1) 3 n →∞ ( 3n + 1) ( 3n − 1)

2

9)  lim

8)  lim

13)  lim

(3n

3n 2 + 2n + n 6)  lim n→∞ − 2n 2 + 5n + 2

3n 5 − 2n 3 + 6n − 4 n → ∞ − n 6 + 2 n 5 − 3n + 4

1 2 n − 5n + 6 10 − 8n n + 2 n 10)  lim n →∞ 4n 3 + n 2 − 2 7)  n → ∞

19) 

3)  lim x →∞

2) lim  4 −

(

n 2 + 4 n + 1 − n 2 + 8n + 1

1 + 2 + 3 + ... + n n →∞ 3n 2 − 1

21)  lim

 n+9   n →∞ 2n − 7  

24)  lim 

 2n + 3  27)  lim   2 n →∞  n 

3n

n +1

1   33)  lim 1 +  n →∞  5n 

1   3n − 2 

2 n −3

−n

2 +3   3 n + 2 2 n −1   

30)  lim  n →∞

2n

n

 n →∞ 

36)  lim 1 +

1   n2 

−n n +1

−n

n

 4n − 2  38)  lim   n → ∞ 4n − 3  

4 n +3

 n 3 + 2n − 1   39)  lim  3 2 n →∞ n + n  

1    41)  lim 1 − n→∞ n 

n+ 2

 3n − 1  42)  lim 5   n →∞  3n + 1 

 n−5  44)  lim   n →∞ n + 1  

n

 n 3 + 2n + 5   47)  lim  3 n → ∞ n + 5n + 2   

 2 − 3n  45)  lim   n →∞ 5 − 3n   3 n 2 + 3 n +1

48)  lim 1 + 1  n →∞ n 

n

2 n −1

 1 n⋅ 1+   n

n

n

)


límits de successions